Relationship between gambling behaviors and reasons for gambling and aggression levels of young adult sports spectator - Dogukan Batur Alp Gulsen; Serkan Zengin; Erdi Kaya; Ummugulsum Ekinci; Burcu Fidel (ROL Spor Bilimleri Dergisi)
The aim of the study is to examine the relationship between gambling behaviors and reasons and aggression levels of sports spectators in young adulthood. Relational survey model, one of the descriptive research methods, was used in the study. The demographic information form prepared by the researcher was used as the data collection tool in order to access the demographic information of the participants. In the study, the Reasons for Gambling Scale, the Gambling Related Cognitions Scale and the Buss-Perry Aggression Scale were used to examine the aggression levels of the participants. Percentage, frequency, mean, minimum and maximum values were used for descriptive statistics. Pearson correlation coefficient was calculated to examine the relationship levels. The findings of the study revealed significant relationships between the sub-dimensions of the aggression scale and the sub-dimensions of the reasons for gambling scale and the cognitions about gambling scale.